An Overview of Impact of Agrochemicals on Human Health and Natural Environment - Said, Mohamed (Scientific Research Communications, 2023)
Agrochemicals exposure periods and levels, types of agrochemicals used and various environmental condition of the areas are factors for acute and chronic poisoning on human health and environment. Although agrochemicals are the result of modern technology that depends on inorganic fertilizers and pesticides, their continuous use against agricultural pest and disease vectors poses serious threats upon both human health and environment. Overuse of these chemicals have severe effects on human and environment that may lead to immediate and long-term effects. In developing countries, it is very difficult to find out the impact on the environment due to lack of awareness, training, and adequate knowledge for using agrochemicals. Investigating farmer’s awareness of agrochemicals residues and their behaviors regarding application is important in order to reduce human factors that negatively affect environmental safety. This review focuses on a summary of both national and international studies regarding the impact of pesticide and chemical fertilizer residues on nature, both human and environment. The review has revealed the hazardous effects like cancer, neural disorders, and other health related problems and environmental risks associated with agrochemicals exposure.